Pengaruh Model Pembelajaran Kooperatif Tipe Group Investigation Terhadap Kreativitas Mahasiswa Semester I PGSD UM Surabaya pada Mata Kuliah Pengantar Manajemen Pendidikan: The Influence of the Cooperative Learning Model Type of Group Investigation on the Creativity of Semester I Students of PGSD UM Surabaya in the Introduction to Education Management Course - Mirnawati, Lilik Binti (Pedagogia : Jurnal Pendidikan, 2017)
The indicators of creativity consists of fluent, flexible, and original thinking in which the score or value totaled and analyzed by using t-test two independent samples. On the validity of the test, it is obtained that the counting of ≥ r r-critical (0.334), which is item 1= 0.937 and item 2 = 0.885 then the instrument is said to be valid and can be used. In the test of reliableility, the counting of r > r critical (0.60), namely Alpha value of 0.781 means greater than 0.60. Thus the entire item instrument is reliable. The results of hypothesis testing can be seen from the data that has been analyzed by t 5.222> t-table 2.00 (α = 0.05). it can be concluded that the problability of error in this research still below 0,05. Hypothesis testingbcan be decided that with the high price of 5.564 t-test has a significant level of 0.000 which turned the position which is still far below the value of α = 0.05. Therefore, this research successfully rejects the significant level of 5%. Furthermore, it can be concluded that was proved right. Mean posttest in the experimental group was 85.63. The mean post-test control group was 75.45. It can be concluded that the creativity or creative thinking ability of students in the experimental group was higher than the control group. It is mean that model of cooperative learning type group investigation positive effect on creativity or creative thinking students’ ability.